Impacto da prematuridade no comprimento dos telômeros em crianças - Zatti, Helen (2015)
Objective: Assess the impact of prematurity on telomere length, a cell aging marker, in children born with very low birth weight. Methods: We conducted a controlled cross-sectional study evaluating 91 children between 7 and 12 years, been 46 former very low birth weight premature and 45 controls. The relative quantification of the size of telomeres (T/S) was performed by polymerase chain reaction (PCR) in peripheral blood leukocytes. Information on perinatal variables, socioeconomic status and stressful life events were obtained. The linear regression model was used for statistical analysis, both in univariate and multivariate analysis. Results: There was no significant difference in the leukocyte T/S ratio among premature infants and controls (p = 0.841), even after adjustment for possible predictor variables. Univariate analysis showed no statistically significant association between T/S ratio and sex, age, parental age, smoking during pregnancy, education of the caregiver and the head of the family and stressful events that occurred last year. Among preterm infants, there was no relationship between the T/S ratio and birth weight below 1,000 g (β=0.133, 95% CI= -0.141 to 0.406; p=0.341)), gestational age below 30 weeks (β=0.030, 95% CI= -0.209 to 0.270; p=0.34) or bronchopulmonary dysplasia (β = 0.213, 95% CI = -0.166 to 0.591; p=0.15). Conclusions: The results indicate that there is no relationship between preterm birth or very low birth weight and the leukocyte telomere length at school age. However, the findings need to be replicated, preferably in longitudinal studies.